Stress-Coping Strategies and Factors Related Distress among Japanese Physicians - Yuichiro OTSUKA; Yoshitaka KANEITA; Osamu ITANI; Sachi NAKAGOME; Maki JIKE; Takashi OHIDA (Tehran University of Medical Sciences, 2020)
N A